2021
DOI: 10.1093/jpe/rtab100
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between invasive plants and heavy metal stresses: a review

Abstract: Global changes have altered the distribution pattern of the plant communities, including invasive species. Anthropogenic contamination may reduce native plant resistance to the invasive species. Thus, the focus of the current review is on the contaminant biogeochemical behavior among native plants, invasive species and the soil within the plant-soil ecosystem to improve our understanding of the interactions between invasive plants and environmental stressors. Our studies together with synthesis of the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Maintaining the stability of the biogeochemical cycle of N and P is therefore of great significance to entire ecosystems. However, anthropogenic-mediated disturbances of N and P can have a major influence on the structure and functioning of ecosystems; for example, excessive emissions of N and P change the element compositions and stoichiometries in regional ecosystems and the relationships between species composition and ecological processes [4][5][6]. At the same time, invasive alien species (IAS) also pose a serious threaten to ecosystems, which may cause disturbances in biogenic element cycles, reduced biodiversity, ecosystem degradation, and even destruction of the original ecosystem [7].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the stability of the biogeochemical cycle of N and P is therefore of great significance to entire ecosystems. However, anthropogenic-mediated disturbances of N and P can have a major influence on the structure and functioning of ecosystems; for example, excessive emissions of N and P change the element compositions and stoichiometries in regional ecosystems and the relationships between species composition and ecological processes [4][5][6]. At the same time, invasive alien species (IAS) also pose a serious threaten to ecosystems, which may cause disturbances in biogenic element cycles, reduced biodiversity, ecosystem degradation, and even destruction of the original ecosystem [7].…”
Section: Introductionmentioning
confidence: 99%
“…S. gigantea has spread throughout Europe since the nineteenth century and it currently is permanently established in many natural and anthropogenic habitats (Tokarska-Guzik et al 2012;Szymura et al 2018); therefore, its suitability for application, e.g., in bioindication as well as its contribution to metal transfer to food chains are worth consideration. In addition, biogeochemical studies may shed more light on the explanation of its invasiveness: it has already been suggested that increased environmental pollution provides more opportunities for the invasion of alien species (Li et al 2021) and that invasive plants in metal-polluted urban environments may be even more successful than in natural sites due to the better adaptation or tolerance to stressful conditions compared to native plants (Yang et al 2007;Sołtysiak et al 2014). According to Li et al (2021) invasive plants showed self-protective mechanisms when exposed to heavy metals and metal pollution may favor plant invasion due to the widespread higher tolerance of invasive plants to heavy metals compared to native species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biogeochemical studies may shed more light on the explanation of its invasiveness: it has already been suggested that increased environmental pollution provides more opportunities for the invasion of alien species (Li et al 2021) and that invasive plants in metal-polluted urban environments may be even more successful than in natural sites due to the better adaptation or tolerance to stressful conditions compared to native plants (Yang et al 2007;Sołtysiak et al 2014). According to Li et al (2021) invasive plants showed self-protective mechanisms when exposed to heavy metals and metal pollution may favor plant invasion due to the widespread higher tolerance of invasive plants to heavy metals compared to native species. On the other hand, accumulation of anthropogenic pollutants by invasive species has been reported to influence the weed biological control system.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, F. japonica outcompetes native plants for resources such as light and nutrients by forming dense stands and altering the soil nitrogen composition, finally reducing biodiversity [ 17 ]. The success of invasive plants is often related to a higher tolerance toward heavy metals, relative to native species [ 18 ]. In support of this general statement, members of the genus Fallopia have been shown to be tolerant to heavy metal contamination including copper [ 19 ], which is accumulated mainly in roots ( F. convolvulus [ 20 ], F. japonica [ 21 , 22 , 23 ]).…”
Section: Introductionmentioning
confidence: 99%